Pertanggungjawaban Pidana Terhadap Pelaku Pencurian dengan Pemberatan : (Studi Kasus Putusan Nomor 1382/Pid.B/2023/PN Mdn) - Maniar Nainggolan; Endhita Putri; Putri Jesika; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (Universitas 17 Agustus 1945, 2023)
The aim of this research is to find out how criminal responsibility is for perpetrators of theft with weights in the Legal Area of ​​the Medan District Court. The research method used is a normative legal method with a type of normative juridical research, where research focuses on studying the application of rules or norms in positive law. The results of this research show that the criminal and his partner were legally proven and promised to be guilty of committing the crime of